Monoclinic elastic and piezoelectric properties of Rochelle salt. Description within the modified Mitsui model - Levitskii, R.R.; Zachek, I.R.; Moina, A.P. (Condensed Matter Physics, 2005)
We propose a modification of the two-sublattice Mitsui model that takes into
account a coupling with diagonal components of the strain tensor. Within
the developed model, we calculate the piezoelectric and elastic characteristics
of Rochelle salt related to those strains. In the approximation of
zero thermal expansion, we find a set of the model parameters providing a
satisfactory agreement with the available experimental data for the elastic
constants cEij and cEi₄
and for the piezoelectric constants d₁j and g₁j . Запропоновано модифікацію двопідграткової моделі Міцуї, що
враховує взаємодії з діагональними компонентами тензора деформації. В її рамках розраховано пов’язані з цими деформаціями
п’єзоелектричні та пружні характеристики кристалів сегнетової солі.
Проведено числовий аналіз отриманих результатів. У наближенні
нульових теплових деформацій знайдено набір параметрів теорії,
який забезпечує задовільний кількісний опис наявних експериментальних даних для пружних сталих cEij and cEi₄ та п’єзомодулів d₁j and g₁j.